Determinants of childhood immunisation coverage in urban poor settlements of Delhi, India: a cross-sectional study. Issue 8 (26th August 2016) - Devasenapathy, Niveditha; Ghosh Jerath, Suparna; Sharma, Saket; Allen, Elizabeth; Shankar, Anuraj H; Zodpey, Sanjay
Abstract : Objectives: Aggregate data on childhood immunisation from urban settings may not reflect the coverage among the urban poor. This study provides information on complete childhood immunisation coverage among the urban poor, and explores its household and neighbourhood-level determinants. Setting: Urban poor community in the Southeast district of Delhi, India. Participants: We randomly sampled 1849 children aged 1–3.5 years from 13 451 households in 39 clusters (cluster defined as area covered by a community health worker) in 2 large urban poor settlements. Of these, 1343 completed the survey. We collected information regarding childhood immunisation (BCG, oral polio vaccine, diphtheria–pertussis–tetanus vaccine, hepatitis B and measles) from vaccination cards or mothers' recall. We used random intercept logistic regression to explore the sociodemographic determinants of complete immunisation. Results: Complete immunisation coverage was 46.7% and 7.5% were not immunised. The odds of complete vaccination (OR, 95% CI) were lower in female children (0.70 (0.55 to 0.89)) and Muslim households (0.65 (0.45 to 0.94)). The odds of complete vaccination were higher if the mother was literate (1.6 (1.15 to 2.16)), if the child was born within the city (2.7 (1.97 to 3.65)), in a health facility ( 1.5 (1.19 to 2.02)), belonged to the highest wealth quintile (compared with the poorest; 2.46 (1.5 to 4.02)) or possessed a birth certificate (1.40 (1.03 to 1.91)). Cluster effect due to unmeasured neighbourhood factors expressed as median OR was 1.32. Conclusions: Immunisation coverage in this urban poor area was much lower than that of regional surveys reporting overall urban data. Socioeconomic status of the household, female illiteracy, health awareness and gender inequality were important determinants of coverage in this population. Hence, in addition to enhancing the infrastructure for providing mother and child services, efforts are also needed to address these issues in order to improve immunisation coverage in deprived urban communities. Trial registration number: CTRI/2011/091/000095.